Perspectives of Maryland Adults Regarding Caries Prevention - Horowitz, Alice M. (Am J Public Health, 2015)
Objectives. We obtained in-depth information from low-income parents and caregivers of young children about their knowledge and understanding of and practices related to the prevention and control of dental caries (tooth decay). Methods. In 2010, we conducted 4 focus groups in Maryland communities with low-income, English-speaking parents and caregivers who had at least 1 child aged 6 years or younger or who were pregnant. We developed a focus group guide based on findings of a previous statewide random telephone survey of adults with young children. Results. Most participants had limited understanding of and extensive misinformation about how to prevent dental caries. They were confused about the use of juice and its impact on their child’s teeth and had limited understanding of the use of fluorides to prevent caries. Most did not drink tap water and did not give it to their children; rather, they used bottled water. Conclusions. These results and those of the statewide telephone survey strongly suggest the need for educational interventions designed for those with limited levels of education.